Immobilization of aldehyde reductase for the production of bioplastic precursors from agricultural fatty acids - Mohne, Devesh; Reddy, Yeddula Nikhileshwar; Rawat, Kshitij; Patil, Mahesh D.; Bhaumik, Jayeeta (RSC Sustainability, 2025)
<div class="abstract author" id="aep-abstract-id6" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Herein, we report the biosynthesis of bioplastic precursors thourgh the immobilization of aldehyde reductase (AHR) onto a metal organic framework (UIO-66-NH2). Kinetic analysis demonstrated that the immobilized AHR maintained significant catalytic activity and exhibited improved operational stability, as well as higher reusability, compared with the free AHR. Furthermore, the synthetic applicability of the immobilized AHR was evaluated in tandem with that of transaminase derived from S. pomeroyi (spTA), where 8, 10, and 12 carbon chain ω-amino fatty acids (ω-AFAs) were biosynthesized from the corresponding hydroxy fatty acids (ω-HFAs) with ∼90% conversions. <div class="abstract graphical" id="aep-abstract-id8" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Herein, we report the biosynthesis of bioplastic precursors via the immobilization of aldehyde reductase (AHR) onto a metal organic framework (UIO-66-NH2).